2014
DOI: 10.1590/s0103-84782014000300027
|View full text |Cite
|
Sign up to set email alerts
|

Características fermentativas de silagens de cana-de-açúcar com erva-sal

Abstract: RESUMO Objetivou-se com o presente estudo avaliar diferentes níveis (0, 20, 40 e 60%)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
1
0
1
2
Order By: Relevance
“…Researchers reported higher CP contents at younger ages when studying the bromatological composition of sugarcane harvested at 18 and 12 months old, respectively [21,22], corroborating the result found in this research. For the most part, CP is concentrated in the leaves, which are abundant in the early stage of sugarcane development in March and May.…”
Section: Forage Chemical Compositionsupporting
confidence: 86%
See 1 more Smart Citation
“…Researchers reported higher CP contents at younger ages when studying the bromatological composition of sugarcane harvested at 18 and 12 months old, respectively [21,22], corroborating the result found in this research. For the most part, CP is concentrated in the leaves, which are abundant in the early stage of sugarcane development in March and May.…”
Section: Forage Chemical Compositionsupporting
confidence: 86%
“…The ash content observed in the fresh silage was lower than that found by Silva JG et al [22] in a study of sugarcane silage without the use of additives (4.58%). The authors observed a 0.17% increase in ash content for each 1.0% increase of old man saltbush (Atriplex nummularia L.) in sugarcane silage.…”
Section: Silage Chemical Compositioncontrasting
confidence: 71%
“…SILVA et al (2014), em estudo de associação da erva sal na ensilagem de cana-de-açúcar, também observaram efeito linear crescente no teor de material mineral dessas silagens, melhorando tanto sua composição química quanto as características fermentativas.…”
Section: ----------Níveis De Taboa (%)----------unclassified
“…Segundo SILVA et al (2014), maiores concentrações de minerais na massa ensilada, concorrem para uma alta pressão osmótica, o protoplasma das células dos microrganismos se desidrata, havendo contração da membrana plasmática (plasmólise). Em virtude disso, o desenvolvimento de microrganismos indesejáveis é inibido (REZENDE et al, 2011).…”
unclassified